The Appropriateness of Unbiased Optical Fractionators to Assess Cell Proliferation in the Adult Hippocampus - Noori, Hamid Reza; Fornal, Casimir Adam (Frontiers in Neuroscience, 2011)
Optical fractionators have dominated the field of neural cell counting for two decades. These unbiased stereological techniques are often used for the quantification of hippocampal cell proliferation in neurogenesis experiments. However the heterogeneous distribution of labeled cells, especially in the form of clusters, confounds the application of these techniques. A critical evaluation of the applicability of the optical fractionator suggests that absolute counting achieves higher efficiency in the quantification of cell proliferation than unbiased estimations.